1980
DOI: 10.1126/science.7361117
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Deficiency Produces Spasms of Coronary Arteries: Relationship to Etiology of Sudden Death Ischemic Heart Disease

Abstract: Isolated coronary arteries from dogs were incubated in Krebs-Ringer bicarbonate isolation and exposed to normal, high, and low concentrations of magnesium in the medium. Sudden withdrawal of magnesium from the medium increased whereas high concentrations of magnesium decreased the basal tension of the arteries. The absence of magnesium in the medium significantly potentiated the contractile responses of both small and large coronary arteries to norepinephrine, acetylcholine, serotonin, angiotensin, and potassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
0
3

Year Published

1982
1982
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(171 citation statements)
references
References 21 publications
8
160
0
3
Order By: Relevance
“…In a recent in vitro strudy, we demonstrated that acute withdrawal of magnesium induces contractile responses in canine coronary arteries (Turlapaty & Altura, 1980). Furthermore, we also demonstrated that magnesium withdrawal potentiated the contractile responses of coronary arteries to various vasoactive agents which have been implicated, clinically, in induction of coronary vasospasm.…”
Section: Litroductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In a recent in vitro strudy, we demonstrated that acute withdrawal of magnesium induces contractile responses in canine coronary arteries (Turlapaty & Altura, 1980). Furthermore, we also demonstrated that magnesium withdrawal potentiated the contractile responses of coronary arteries to various vasoactive agents which have been implicated, clinically, in induction of coronary vasospasm.…”
Section: Litroductionmentioning
confidence: 82%
“…Since it is known that vasoactive agents utilize different sources of calcium (Ca) for their contractile responses (Weiss, 1978), it has been suggested that in a magnesium-deficient state, Ca2' influx might be enhanced, thereby resulting in an increased tone and contractility (Altura & Altura, 1974;1978;1981;Altura, 1979;Turlapaty & Altura, 1980). It is also possible that Mg2+-deficiency might increase the sensitivity of postsynaptic receptors, as it has been shown by several investigators that Mg2e can alter the sensitivity of non-cardiac blood vessels to several neurohumoral I©The Macmillan Press Ltd 1982 substances (Somlyo, Woo & Somlyo, 1966;Altura & Altura, 1971;1978;Altura, 1975;Turlapaty, Carrier & Jurevics, 1975;Altura, Altura & Waldemar, 1976;Goldstein & Zsoter, 1978).…”
Section: Litroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…98,99 Hypomagnesemia has also been shown to cause an increase in coronary vascular reactivity and could potentially accelerate plaque rupture. 100,101 Ang II can trigger most of the changes reported to be associated with magnesium deficiency, including induction of pro-oxidant and proinflammatory conditions. 102 Moreover, Ang II induces the synthesis of plasminogen activator inhibitor type 1 in endothelial cells.…”
Section: Plaque Stabilizationmentioning
confidence: 99%
“…Serotonin receptor activity is altered by changes in levels of ionized Mg +2 [31,32] and vasoconstriction induced by serotonin can be effectively blocked by pretreatment with Mg +2 [33]. Experimental Mg +2 deficiency leads to generation and release of substance P [34] which is thought to act on sensory fibers and cause the pain in headache [35].…”
Section: Discussionmentioning
confidence: 99%